Analisis Kaidah Fiqhiyyah Al-ʿādah Muḥakkamah Terhadap Konsep Perjanjian Perkawinan dalam Hukum Islam - Lenny Guspidawati; Hendri Sayuti (JURNAL ILMIAH NUSANTARA, 2026)
A marriage contract is a legal instrument that formalizes an agreement between husband and wife regarding certain aspects of married life, particularly those related to property, rights, and obligations. Within the framework of Islamic law, this concept receives significant attention from the perspective of qawāʿid fiqhiyyah, as both serve as methodological foundations for interpreting and applying Sharia law in accordance with maqāṣid al-sharīʿah. This article aims to analyze the concept of prenuptial agreements using an applied approach through qawāʿid fiqhiyyah to practical legal cases, as well as a conceptual and epistemological approach through uṣūl al-fiqh. Using descriptive qualitative methods and a literature review of classical sources such as al-Ashbāh wa al-Naẓāʾir by Imam al-Suyūṭī and al-Muwāfaqāt by Imam al-Shāṭibī, this study finds that prenuptial agreements have a valid Sharia basis as long as they do not conflict with the basic principles of Islamic law. Analysis based on legal principles such as al-ʿādah muḥakkamah (custom has legal force) shows the flexibility of Islamic law in accommodating socio-legal needs. From a fiqh perspective, this concept is in line with the objectives of Sharia in protecting property (ḥifẓ al-māl) and offspring (ḥifẓ al-nasl). Therefore, prenuptial agreements are not only administrative tools, but also reflect the implementation of Sharia values in family life.